PERANAN REFORMASI BIROKRASI DI INDONESIA DALAM MEWUJUDKAN âGOOD GOVERNANCE â - Bajuri, Diding (Jurnal Ilmu Administrasi CENDEKIA, 2016)
Bureaucracy in most developing countries is generally classified as a closed bureaucracy. Bureaucracy rarely open, but there is a tendency to become bureaucratic mix. Therefore, administrative reform must start with reforms that are pragmatic in order to open the closure of the bureaucracy. But in reality, many developing countries that started the reform-oriented activities on the technique. As a result, many are experiencing failure and frustration.